Implementation of Web-based Electrical Appliance Installation Monitoring: TAM Testing Approach - Suthirta, Kev Michael; Witno, Suwitno (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The development of technology in the business world can have a positive impact, simplifying the way companies manage their operations and improving business performance through the implementation of systems. A web-based information system for monitoring activities within the company was designed using the Laravel Framework to address inefficiencies in the current manual monitoring process. The existing system requires on-site visits for monitoring and uses paper-based reporting, which is inefficient, prone to disorganized or lost reports, and time-consuming. The proposed solution is the development of a system using the Laravel framework and the Waterfall methodology. The system design was evaluated using the Technology Acceptance Model (TAM), focusing on three variables: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioral Intention to Use (BITU). The evaluation process involved three stages: determining the variables, defining indicators, and creating a questionnaire. A total of 54 questionnaires were distributed and processed using the SmartPLS4 application. The results revealed that perceptions of the system's ease of use significantly influence users' behavior to continue using the Web-Based Monitoring System for Electrical Equipment Installation. Additionally, the perceived ease of use impacts the perception of the system's usefulness, and the perception of usefulness also affects users' behavioral intention to repeatedly use the system.